Structural health monitoring of scarf bonded repaired glass/epoxy laminates interleaved with carbon non-woven veil - Ozan Can Zehni; Oğuzcan İnal; Kali Babu Katnam; Mark A. Bissett; Ian A. Kinloch (Composites Part C: Open Access)
Bonded repair patches/joints often introduce vulnerabilities in composite laminates, making them prime candidates for structural health monitoring (SHM). In this study, stepped-scarf bonded joints were manufactured using glass fibre-reinforced epoxy laminates as representative repair patches, and a novel SHM approach through the electrical resistance change method was applied. To establish an electrically conductive path within the stepped-scarf joint, non-woven carbon fibre veils with areal weights of 10 g/m² and 20 g/m² were interlaid along the stepped bondline. Two types of tensile tests were performed. In the first set of tests, the stepped-scarf joints underwent monotonic quasi-static tensile loading until the bondline was completely fractured (catastrophic failure) and the change in electrical resistance was continuously monitored. The failure stress of the joint with a 10 g/ m² carbon veil was only marginally decreased (∼2 %) in comparison with that of the joints without a carbon veil, while the failure stress of the joint with a 20 g/m² carbon non-woven veil was considerably decreased (by ∼9 %). However, the joints with 10 g/m² and 20 g/m² carbon veils exhibited a significant change in electrical resistance (∼200 % and ∼1000 %, up to full failure, respectively). Simultaneously, the change in electrical resistance was used for the detection of damage initiation and progression, supported by digital images taken during the tests. In the second set of tests, the joints were subjected to a cyclic tensile loading/unloading regime and the change in electrical resistance was monitored. A significant amount of permanent change in resistance during the unloading phases (up to 120 % in the bondline with a 20 g/m² veil) was observed, providing insights into the laminate and bondline damage evolution. In addition, thermal images obtained with the joule heating method in the cyclic tensile tests were used to confirm the damage detected with the electrical resistance change method. Moreover, the micrographs from the fracture surfaces indicated that the variations in electrical resistance change are largely caused by damage occurring within or near the carbon veils. In conclusion, the results demonstrate that the presented SHM approach, which incorporates carbon non-woven fibre veils within non-conductive laminate composites, holds promise for monitoring damage initiation and propagation in repaired composite laminates as well as adhesively bonded composite laminate joints, without adversely influencing the structural integrity of the bondline.